2021
DOI: 10.3390/su13147654
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Tax Aggressiveness in Family Firms: An Investigation of Italian Private Family Firms

Abstract: A recent stream of research has focused on tax aggressiveness, the downward management of taxable income through tax planning activities, and has analyzed its antecedents and consequences, mainly on public companies. Only very few studies, however, have been carried out in the context of private family business and have investigated whether some family firms are more tax aggressive than others, considering some specific features of family firms, such as their distinctive agency conflicts and socioemotional wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 93 publications
(178 reference statements)
3
17
0
Order By: Relevance
“…S anchez-Mar ın et al (2016), Brune et al (2019b) and Bauweraerts et al (2020) show that, depending on the percentage stake owned by the family, closely-held family firms are less tax aggressive. However, Kovermann and Wendt (2019) and Flamini et al (2021) showed, on the contrary, that the higher the family's ownership percentage, the higher the tax aggressiveness behaviour.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…S anchez-Mar ın et al (2016), Brune et al (2019b) and Bauweraerts et al (2020) show that, depending on the percentage stake owned by the family, closely-held family firms are less tax aggressive. However, Kovermann and Wendt (2019) and Flamini et al (2021) showed, on the contrary, that the higher the family's ownership percentage, the higher the tax aggressiveness behaviour.…”
Section: Introductionmentioning
confidence: 79%
“…The first is agency theory, which has been used to explain the behaviour of listed family firms (Chen et al, 2010;Mafrolla and D'Amico, 2016;Brune et al, 2019a, b), which engage in less tax aggressive behaviour in order to send clear signals to financial markets and avoid such undesirable consequences as a potential share price discount. Agency theory also explains how private family businesses, especially closely-held ones, manage principal-toprincipal conflicts (L opez-Gonz alez et al, 2019;Flamini et al, 2021). The second theory in the specialised literature invokes Socioemotional Wealth (SEW) to explain how the involvement of the family in ownership and management leads to less tax aggressive behaviours (Steijvers and Niskanen, 2014;L opez-Gonz alez et al, 2019).…”
Section: Family Business and Tax Managementmentioning
confidence: 99%
See 3 more Smart Citations